Modern Non-Steroidal Anti-Inflammatory Drugs - Bekchanov Bakhtiyar Gafurovich; Masharipov Otaboy Olimovich; Komilova Dilrabo Rakhimboy qizi; Masharipov Ogabek Atabaevich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Over the past decade, employees of the departments of pharmacology, general and bioorganic chemistry of the Tashkent State Medical Institute (since 1990, I Tashkent State Medical Institute) have been conducting targeted research to find, study new, more advanced anti-inflammatory drugs in a number of new pyrazole derivatives and related compounds (in general, nutrition more than 300 new drugs were exposed). These studies revealed a number of highly active and low-toxic compounds, and also established the dependence of the anti-inflammatory activity of these compounds on the chemical structure.